Analisis Efektivitas Pengelolaan BUMNag Berkah Mandiri dalam Meningkatkan Pendapatan Asli Nagari Bukit Tandang Kecamatan Bukit Sundi Kabupaten Solok - Aprilia Shelina; Novera Martilova (Transformasi: Journal of Economics and Business Management, 2024)
This research aims to assess and analyze the success of the management of BUMNag Berkah Mandiri in increasing the original income of Nagari Bukit Tandang. The research method used is qualitative research. The findings of this research indicate that the effectiveness of the management of BUMNag Berkah Mandiri in increasing the original income of Nagari Bukit Tandang is quite effective in providing a contribution in the form of original income of Nagari to the government of Nagari Bukit Tandang. Judging from 3 indicators, namely goal achievement, adaptation and integration, not all have been achieved optimally. The results of the research show that the achievement of the goals of BUMNag Berkah Mandiri has not yet achieved the expected goals but has been able to make a small contribution to increasing the original income of Nagari Bukit Tandang, and the indicators of adaptation and integration have been running perfectly because the business units in BUMNag Berkah Mandiri are already in place. in accordance with the needs of the people of Nagari Bukit Tandang. However, behind that, there are of course obstacles that hinder the management of BUMNag Berkah Mandiri in increasing the original income of Nagari, namely the constraints on the management itself and the lack of support from the people of Nagari Bukit Tandang in developing the existing business units at BUMNag Berkah Mandiri.